2010
DOI: 10.1093/ndt/gfq623
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to guidelines in peritoneal dialysis

Abstract: International variation in guideline adherence may be influenced by a country's healthcare expenditure, physician's PDA use and experience, and size of PD practice which may impact future guideline development and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The literature review found limited previous research exploring the control variables and EBP use for providers. One study showed that shorter length of clinical practice for physicians was significantly associated with an increased use in evidence‐based medicine guidelines (Allen et al, ). The results of this study using age as a proxy for clinical experience did not support this previous finding.…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…The literature review found limited previous research exploring the control variables and EBP use for providers. One study showed that shorter length of clinical practice for physicians was significantly associated with an increased use in evidence‐based medicine guidelines (Allen et al, ). The results of this study using age as a proxy for clinical experience did not support this previous finding.…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…Our survey was distributed to Nephrology Now subscribers with survey methodology and population surveyed described elsewhere (please see additional file 1 for the original survey instrument) [ 10 , 11 ]. In brief, Nephrology Now is a non-profit, online, free email alert service that selects nephrology journal articles and incorporates them into a monthly mailing list http://www.nephrologynow.com .…”
Section: Methodsmentioning
confidence: 99%
“…However, in particular, in private settings, or under strong cost constraints, treatment choices may be affected by the reimbursement system, which is graded for levels of care in many countries. Indeed, reimbursement is often higher for in-hospital and lower for home-based treatments, a policy that tends to disincentivize home dialysis in all its forms [ 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%